The effects of selective amygdalohippocampectomy on episodic memory, spatial representation and discourse production among human neurological patients - Mangaoang, Maeve (Trinity College (Dublin, Ireland). School of Psychology, 2004)
The work described in this thesis is directed at investigating the neuropsychological effects of damage to the medial temporal lobes among a group of patients who have undergone surgery for the relief of medically intractable temporal lobe epilepsy (TLE). This investigation focuses on a specific neurosurgical procedure, termed selective amygdalohippocampectomy (SAH) and the effects of this procedure on episodic memory, spatial representation, spatial navigation, and discourse production. The main method of enquiry involves the assessment of postoperative patients on a variety of novel tasks, which were designed to be sensitive to hippocampal damage. A brief synopsis of the work contained in each chapter of this thesis is presented below.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin